2008
DOI: 10.1890/06-1926.1
|View full text |Cite
|
Sign up to set email alerts
|

NO EVIDENCE FOR TRADE-OFFS:CENTAUREAPLANTS FROM AMERICA ARE BETTER COMPETITORS AND DEFENDERS

Abstract: The natural enemies hypothesis has led to a number of ideas by which invaders might evolve superior competitive ability. In this context, we compared growth, reproduction, competitive effect, competitive response, and defense capabilities between invasive North American populations of Centaurea maculosa and populations in Europe, where the species is native. We found that Centaurea from North America were larger than plants from European populations. North American Centaurea also demonstrated stronger competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
156
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 63 publications
20
156
2
2
Order By: Relevance
“…However, experimental conditions can markedly affect the concentration of the bio-available fraction of flavonoids. This has been found to range from 0 to 2.4 (Blair et al 2005), 5 to 35 (Weir et al 2003), 0 to 113 (Ridenour et al 2008), and 83 to 185 μg ml −1 (Bais et al 2002). These variable data are likely due to the efficiency of the extraction method and soil type.…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental conditions can markedly affect the concentration of the bio-available fraction of flavonoids. This has been found to range from 0 to 2.4 (Blair et al 2005), 5 to 35 (Weir et al 2003), 0 to 113 (Ridenour et al 2008), and 83 to 185 μg ml −1 (Bais et al 2002). These variable data are likely due to the efficiency of the extraction method and soil type.…”
Section: Introductionmentioning
confidence: 99%
“…Some generalist herbivores prefer native plants over exotic plants (Cappuccino and Carpenter, 2005;Han et al, 2008;Ridenour et al, 2008;Tallamy et al, 2010). Herbivores from Portuguese coast, including gastropods (Gibbula umbilicalis, Gibbula pennanti), sea hare (Aplysia punctata), and sea urchin (Paracentrotus lividus) prefer native seaweeds, Laminaria ochroleuca, Bifurcaria bifurcata, Mastocarpus stellatus, Chondrus crispus, and Osmundea osmunda, and avoid the invasive Sargassum muticum (Monteiro et al, 2009).…”
Section: Exotic Plant Defense Against Generalist Herbivoresmentioning
confidence: 99%
“…Exotic plants are also less likely to be attacked by generalist herbivores in introduced ranges (Mü ller-Schärer et al, 2004;Schaffner et al, 2011). In the absence of specialist herbivores in introduced ranges, resources previously allocated to plant defense in the native range might get reallocated to: (1) growth or reproduction of the exotic plant, so leading to enhanced competitiveness, as suggested by the evolution of increased competitive ability hypothesis (EICA; Blossey and Nö tzold, 1995;Bossdorf et al, 2005;Ridenour et al, 2008), (2) the production of less-costly chemical compounds such as terpenes and glucosinolates, as predicted by the shift in defense hypothesis (SDH; Doorduin and Vrieling, 2011), and/or (3) the higher production of allelochemicals novel for invaded communities, as assumed by the novel weapons hypothesis (NWH; Callaway and Ridenour, 2004;Supplemental Box S1).…”
mentioning
confidence: 99%
“…For examples, Oduor et al (2011) found that the invasive populations of Brassica nigra s resisted against herbivore better than native ones. Introduced populations of Defense against both specialists and generalists of introduced populations of Centaurea maculosa (Asteraceae) were better than their native counterparts (Ridenour et al, 2008). In addition, the invasive Verbascum thapsus populations grew better than the native ones but the defense between the two range were remarkably similar (Alba et al, 2011).…”
Section: Introductionmentioning
confidence: 99%